Highly Reversible Supramolecular Light Switch for NIR Phosphorescence Resonance Energy Transfer. Issue 2 (5th November 2021) - Wang, Conghui; Ma, Xin‐Kun; Guo, Peng; Jiang, Chunhui; Liu, Yao‐Hua; Liu, Guoxing; Xu, Xiufang; Liu, Yu
Abstract: Although purely organic room‐temperature phosphorescence (RTP) has drawn widespread attention in recent years, regulatable phosphorescence resonance energy transfer (PRET) supramolecular switch is still rare. Herein, single molecular dual‐fold supramolecular light switches, which are constructed by phenylpyridinium salts modified diarylethene derivatives (DTE‐Cn, n = 3, 5) and cucurbit[8]uril (CB[8]) are reported. Significantly, biaxial [3]pseudorotaxane displayed efficiently reversible RTP after binding with CB[8] and the phosphorescence quenching efficiency is calculated up to be 99%. Furthermore, the binary supramolecular assembly can coassemble with Cy5 to form ternary supramolecular assembly showing efficiently PRET, which is successfully applied in switchable near infrared (NIR) mitochondria‐targeted cell imaging and photocontrolled data encryption. This supramolecular strategy involving energy transfer provides a convenient approach for phosphorescent application in biology and material fields. Abstract : A switchable supramolecular phosphorescence resonance energy transfer system for NIR cell imaging and data encryption is reported. This supramolecular strategy involving energy transfer provides a convenient approach for phosphorescent application in biology and material fields.